Treatment Planning for Person-Centered Care : Shared Decision Making for Whole Health - Adams, Neal.; Grieder, Diane M.; ScienceDirect eBooks (London : Academic Press, 2014)
This book guides therapists in how to engage clients in building and enacting collaborative treatment plans. It provides practical guidance on how to organize and conduct the recovery plan meeting, prepare and engage individuals in the treatment planning process, help with goal setting, use the plan in daily practice, and evaluate and improve the results.
Section I. Land of opportunity -- section II. Getting started -- section III. On the road -- section IV. Journey's end : the destination.
Print version record.
Includes bibliographical references and index.
Elsevier
Keywords: Mentally ill -- Care; Addicts -- Rehabilitation -- Planning; Client-centered psychotherapy; Mental Disorders -- therapy; Patient-Centered Care -- organization & administration; Electronic books